POLICY MODELS IN HANDLING BOUNDARY DISPUTES IN TERNATE CITY FROM THE PERSPECTIVE OF LOCAL GOVERNMENT - Bakri La Suhu; Marno Wance; Darwin Abd Radjak; Rasid Pora (Adisam Publisher, 2025)
This research explains and analyses the policy models that have been carried out in handling boundary disputes in Ternate City. There are several policy models that have been carried out by the government and there are also policy models carried out by the Sultanate of Ternate. Of course, the policies that have been carried out by the Sultanate of Ternate are part of local wisdom policies based on the values of the Ternate indigenous people. The results show that the government policy model in handling boundary disputes in Ternate City is through multilevel mediation, starting from village level mediation to the Ternate City government. In addition, there is also a policy model carried out by the Sultanate of Ternate in deciding several options in determining boundaries in accordance with Idin Kolano (Order of the Sultan of Ternate), namely the first option, after opening the location of the Deru-deru Book Landfill (TPA), then the southern landfill boundary with the determination of the Yakis Fruit District (Jambu Monkey) is divided in half between Takome and Sulamadaha, the second option, the entrance to Jiko Malamo is divided in half between Takome and Sulamadaha, and the third option, the landfill location is divided in half between Takome and Sulamadaha.